Phosphoinositide-3-kinases p110α and p110β mediate S phase entry in astroglial cells in the marginal zone of rat neocortex - Müller, Rabea; Fischer, Catharina; Wilmes, Thomas; Heimrich, Bernd; Distel, Vanessa; Klugbauer, Norbert; Meyer, Dieter K. (Frontiers in Cellular Neuroscience, 2013)
In cells cultured from neocortex of newborn rats, phosphoinositide-3-kinases of class I regulate the DNA synthesis in a subgroup of astroglial cells. We have studied the location of these cells as well as the kinase isoforms which facilitate the S phase entry. Using dominant negative isoforms as well as selective pharmacological inhibitors we quantified S phase entry by nuclear labeling with bromodeoxyuridine. Only in astroglial cells harvested from the marginal zone of the neocortex inhibition of phosphoinositide-3-kinases reduced the nuclear labeling with bromodeoxyuridine, indicating that neocortical astroglial cells differ in the regulation of proliferation. The two kinase isoforms p110 and p110were essential for S phase entry. p110 diminished the level of the p27Kip1 which inactivates the complex of cyclin E and CDK2 necessary for entry into the S phase. p110phosphorylated and inhibited glycogen synthase kinase-3which can prevent S-phase entry. Taken together, both isoforms mediated S phase in a subgroup of neocortical astroglial cells and acted via distinct pathways.